Defining the end of puberty in boys: INSL3 and the acute determinants of adult Leydig-cell functional capacity - Tulumcu, Bilal; Ivell, Richard; Alhujaili, Waleed; Anand-Ivell, Ravinder (Frontiers in Endocrinology, 2025)
IntroductionTesticular Leydig cells are responsible for producing almost all the testosterone required by men throughout the lifespan, with reduced testosterone (hypogonadism) correlating with age-linked morbidity and mortality. Leydig cells derive from stem cells within the testes after birth. These undergo proliferation and differentiation during puberty to achieve their final adult status in young adulthood, after which there appears to be no further cell division and only very limited attrition into old age. Leydig-cell functional capacity reflects the total number and differentiation status of the Leydig-cell population within an individual and can be assessed by measuring in blood the constitutive Leydig-cell hormone insulin-like peptide 3 (INSL3). In adult men, this varies by more than 10-fold between individuals and correlates with later morbidity. Such INSL3 variance appears to have its origin already in young men, though what determines this is largely unknown.MethodsHere, we have used the ALSPAC (Avon Longitudinal Study of Parents and Children) cohort of boys and young men to estimate when the adult-type Leydig-cell population becomes established, that is, when puberty ends, and the contemporary anthropometric and lifestyle parameters that influence this.Results and discussionAt 17 years, mean INSL3 is not yet maximal, with high variance due to both longitudinal (timing of pubertal trajectory) and cross-sectional influences, whereas at 24 years, circulating INSL3 concentration has stabilized to its final adult status, even showing a small decreasing trend with age. Maximal INSL3 (i.e., peak puberty) was calculated to be at approximately 22 years in this cohort. Both contemporary body mass index and smoking status, though not inflammatory parameters, were contributory factors to INSL3 concentration. However, the major source of INSL3 variance in young men was shown to be already established at 17 years, with causative influences evidently occurring prior to this age, and showing that early life parameters are important for determining later adult health in men.